Evaluation of the al-qur’an tahfidz program at Al-Azhar Elementary School: efforts to nurture a qur’anic generation from an early age - Yenny Aulia Rachman; Elsa Rahma Adila; Gandhes Sembodro Budy; Junedi; Madya Dr Azlan Shaiful Baharum (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Elementary school is an important foundation in the development of children in Indonesia, especially for those aged 7 to 12 years. During this golden age, elementary school is not only a place where children receive formal education but also a place that shapes character and instills spiritual values that are highly needed in today’s era. One of the efforts undertaken is through the tahfidz program, which serves as a bridge between academic education and character education. Through this program, students are not only taught to memorize verses of the Al-Qur’an but also to understand the meaning and values contained within. However, it must be acknowledged that each student has different memorization abilities, so it is not uncommon for boredom to arise during the learning process. Therefore, this study was conducted to evaluate and improve the effectiveness of the extracurricular tahfidz program. This study uses the CIPP evaluation model (Context, Input, Process, Product), which includes evaluation of the context, input, process, and results of the program. The evaluation results show that the extracurricular tahfidz program at SD Al Azhar is able to improve students' faith, piety, and spiritual quality. This success is supported by a relevant curriculum, adequate facilities and infrastructure, as well as competent teaching staff. Overall, the implementation of this program has been in line with the curriculum and is able to meet the expected educational goals.